The convergence of diversity the European model (Presa Universitară Clujeană, 2014)
"This volum represent the idea of European Studies in Cluj Napoca - interdisciplinarity, multiculturalism and diversity. The volum also represents the personality of prof. univ. dr. Nicolae Păun, a historian at his roots that has developed to one of the leading professors in European Studies in Romania."